Demanda energética em diferentes sistemas de preparo periódico do solo antes e depois da subsolagem - Salvador, Nilson; Benez, Sérgio Hugo [UNESP]; Mion, Renildo Luiz; Viliotti, Carlos Alberto (My University, 2008)
Both the inadequate use and the ignorance of the different soil tillage implements available in the home market has become one of the leading motives of failures, related to soil and water conservation. The periodical tillage is traditionally utilized after subsoiling for soil clod breaking, leveling and residue incorporation. This work aimed to evaluate the energy requirement for different periodical soil tillage systems performed before and after subsoiling in a soil classified as Distroferric Red Nitosol. The periodic tillage systems were: disk plowing; disk plowing plus one leveling harrowing; disk harrow; disk harrow plus leveling harrowing stirring. The experimental design was a 5×2 factorial scheme with 5 completely randomized blocks. The results show that the periodic soil preparation systems based on disks have better energy efficiency when performed before the operation of subsoiling. The system of soil preparation with harrowing obtained the lower energy demand, in relation to other periodic soil preparation systems, when done after subsoiling.
Demand of energy in various systems of regular soil preparation before and after subsoiling
Keywords: Harrow; Plow; Stirrer; Subsoiler; Traction of Force; Tractor